IBAMar Database: Four Decades of Sampling on the Western Mediterranean Sea - A Aparicio-González; J L López-Jurado; R Balbín; J C Alonso; B Amengual; J Jansá; M C García; F Moyá; R Santiago; M Serra; M Vargas-Yáñez (Data Science Journal, 2015)
IBAMar is a regional database that puts together all the physical and biochemical data provided by multiparametric probes and water sample analysis taken during the cruises managed by the Balearic Oceanographic Center of the Instituto Español de Oceanografía (COB-IEO) during the last four decades. Initially, it integrated data from hydrographic profiles obtained from CTDs (conductivity, temperature, depth) equipped with several sensors, but it has been recently extended to incorporate data obtained with hydrocasts using oceanographic Niskin or Nansen bottles. The result is an extensive regional resource database that includies physical hydrographic data such as temperature (T), salinity (S), dissolved oxygen (DO), fluorescence, and turbidity, as well as biochemical data, specifically dissolved inorganic nutrients (phosphate, nitrate, nitrite, and silicate) and chlorophyll-a. Different technologies and methodologies were used by independent teams during the four decades of data sampling. However in the IBAMar database, data have been reprocessed using the same protocols and a standard quality control (QC) methodology has been applied to each variable. The result is a homogeneous and quality-controlled data. IBAMar database at standard levels is freely available for exploration and download from http://www.ba.ieo.es/ibamar/.